Pengaruh Kepemimpinan Kepala Sekolah, Dinamika Budaya Kerja Guru, serta Pengelolaan Sarana dan Prasarana Pendidikan terhadap Kualitas Kinerja Pengajaran Guru - Surianto; Burhanuddin (AL-MUTSLA, 2023)
This study aims to analyze the impact of school principal leadership, teacher work culture, and educational facilities management on teaching performance of Madrasah Ibtidaiyah teachers in Tinambung Subdistrict, Polewali Mandar Regency. Conducted from October to November 2019, it utilized a mixed-method approach, combining qualitative and quantitative methods, with a survey design employing correlational analysis. The population comprised 30 teachers and principals, with a sample size of 30 Madrasah Ibtidaiyah teachers selected through census sampling. Multiple Regression Analysis was employed for data analysis, revealing a significant positive influence of school principal leadership, teacher work culture, and educational facilities management on teaching performance..